Fobia Wajib Pajak Untuk Mengungkapkan Harta - Fellyana Nadia Putri; Umaimah Umaimah (Prodi Akuntansi - FEB Universitas Muhammadiyah Gresik, 2021)
This study aims to reveal the meaning of phobia that is felt by taxpayers in disclosing their assets. This study used a qualitative method with a transcendental phenomenological approach by Edmund Huserl. The number of informants in this study were 3 people including taxpayers, tax authorities and tax consultants. To form informant awareness, data collection was carried out by conducting in-depth interviews with the three informants. The meaning of the phobia revealed is that the taxpayer's phobia in disclosing assets is a form of calculation of profit and loss and a reflection of the taxpayer's faith.